PELATIHAN PEMBELAJARAN DARING PASCA PANDEMI VIRUS COVID-19 DI SMK SARASWATI 3 TABANAN - Ni Putu Parmini,; Ida Bagus Rai Putra,; I Gede Bagus Wisnu Bayu Temaja, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This article aims to report on community service through online learning training during the Covid-19 pandemic at SMK Saraswati 3 Tabanan, Bali. This activity was carried out at the end of 2020. This service used interview, observation, presentation, and lecture methods. This training provides benefits for students and teachers to conduct learning from their respective homes, utilizing communication media such as laptops/mobile phones. The training uses applications such as WhatsApp Group, Google Classroom, Quizizz, Zoom, and others. Students can access learning materials and submit assignments given by teachers without having to meet face to face at school.